Effects of various supplemental levels of multi-enzyme complex on amino acid profiles in egg yolk, antioxidant capacity, cecal microbial community and metabolites of laying hens - Huang, Qixin; Chen, Rui; Wu, Wenzi; Fan, Jinghui; Ma, Xin; Chen, Zhou; Ye, Wenxin; Qian, Lichun (Frontiers in Microbiology, 2024)
This study aimed to investigate the effects of multi-enzyme (alkaline protease, xylanase, glucanase, β-mannanase, cellulase, acid protease, glucoamylase, and α-galactosidase) on antioxidant capacity, egg quality, amino acid profiles in yolk, cecal microflora and metabolites in laying hens. A total of 384 Jingfen No.6 laying hens aged 65 weeks were randomly divided into 4 treatments groups (6 replicates per group) and fed diets containing 0, 150, 300, or 600 mg kg−1 multi-enzyme over an 8-week feeding duration. Our findings revealed that supplementation with 600 mg kg−1 of multi-enzyme significantly increased the albumen height (P < 0.05) and haugh unit (P < 0.05). Moreover, as the levels of multi-enzyme supplementation in the diet increased, there were significant increases in activities of total antioxidant capacity (T-AOC) in serum (P < 0.05) and glutathione peroxidase (GSH-Px) in the liver (P < 0.05). Different levels of multi-enzyme supplementation significantly affected the composition of amino acid profiles in the yolk. Furthermore, the results from 16S rRNA sequencing and untargeted metabolomics analysis of cecal content revealed that multi-enzyme supplementation altered the cecal microflora and metabolite profiles. We found the relative abundance of the Bacteroidota phyla in T600 group was significantly increased (P < 0.05) compared to CON and T150 groups, but the relative abundance of the Firmicutes phylum in T600 group were significantly lower than T150 group (P < 0.05). At the genus level, the relative abundance of the Parabacteroides genera in T300 group, the Faecalibacterium genera in T300 and T600 groups, the norank_f_Prevotellaceae genera in treatment groups (T150, T300 and T600), the norank_f_Peptococcaceae genera in T600 group, and the Monoglobus genera in T1 group were significantly increased. The KEGG pathway analysis showed that the common enrichment metabolic pathways of each treatment group compared to the CON group were glycine, serine and threonine metabolism, foxo signaling pathway and mTOR signaling pathway, and the enrichment metabolic pathways shared by T300 vs CON and T600 vs CON was galactose metabolism and glycolysis/gluconeogenesis pathways. Correlation analysis identified notable relationships between specific microbes and metabolites with T-AOC in serum, GSH-Px activity in the liver, amino acids in yolk, albumen height, and haugh units. Overall, this study suggests that multi-enzyme supplementation regulated the cecal microbial community and metabolism, potentially influencing amino acid profiles in yolk, antioxidant capacity, and egg quality.